Evaluation of UWB antennas at 7-9 GHz for short range wireless communications - Chinabutr, Chatchawin; Promwong, Sathapom (My University, 2018)
Ultra wideband (UWB) impulse radio (IR) signals must be able to accomodate its common frequency band at 7.25 GHz to 8.50 GHz. Moreover, the signals should not be distorted too much when they pass through the antennas. Therefore, the transfer function of antennas must to known for the channel performance. In free space loss is usually evaluated by using the formula of Friis's. However, Friis's formula it's not directly applicable to UWB-IR transmission. This study to presentation, the characterization of UWB-IR transmission in FCC with common frequency band that takes into account the transmission waveform in UWB, its consider the distortion due to the antennas and the correlator receiver. Since the antennas are significant pulse-shaping filters in UWB, various kinds of antennas are experimentally examined, especially focusing on the effect of template waveform receiver.
Keywords: FCC; Friis' transmission formula; IR; UWB; UWB antenna